PERANAN “BUNDO KANDUANG” DALAM SISTEM PEMERINTAHAN DAN SISTEM ADAT DI NAGARI KOTO LAWEH KECAMATAN X KOTO KABUPATEN TANAH DATAR SUMATERA BARAT - Rosi Fitriani; Bedriati Ibrahim; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Minangkabau is one of the tribes and cultures in Indonesian, located in the Sumatera Barat province. The structure of Minangkabau society oeganized according to matrilineal principles, namely a matrilineal. Mother in Adat Minangkabau known as Bundo Kanduang which literally means true mother. Bundo Kanduang can be two categorized, that is: First, as a personality characteristic that refers to the Minangkabau woman as individuals must contributed to the real demands of society. Second, Bundo Kanduang as an institution parallel with other institutions, has the same power and access to the Minangkabau government structure. The purpose of this research is to know (1) Bundo Kanduang in Koto Laweh Village X Koto Subdistrict Tanah Datar Regency Sumatera Barat (2) The role of Bundo Kanduang in the government system in Koto Laweh Village X Koto Subdistrict Tanah Datar Regency Sumatera Barat (3) The role Bundo Kanduang in the customs system in Koto Laweh Village X Koto Subdistrict Tanah Datar Regency Sumatera Barat (4) The prohibition and abstinence Bundo Kanduang in Koto Laweh Village X Koto Subdistrict Tanah Datar Regency Sumatera Barat. The research uses descriptive methode with qualitative approach, and data collection techniques such as observation, interviews, documentation and literature. The result of this research show there are role of Bundo Kanduang in Koto Laweh Village in the village government as well as in the customs.Key Words: The Role, Bundo Kanduang, Government System, Customs System